MEMAHAMI TEORI DAN GAYA KEPEMIMPINAN - M, U. Pg. Fitra A.; Ningsih, Setya; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Anisah, Anisah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Along with the development of social thought and dynamics, various leadership theories have emerged, ranging from classical theories that emphasize the characteristics of individual leaders, to contemporary theories that emphasize situations, interpersonal relationships, and emotional approaches. This study aims to comprehensively examine leadership theories and styles in an institutional context, especially in the educational environment. Through a literature study approach, the author analyzes various leadership styles that have been developed, such as autocratic, directive, participative, transformational, and teaching leadership. The results of the study show that leadership effectiveness is largely determined by the suitability between leadership style and situational context. There is no leadership style that is absolutely perfect, because its effectiveness depends on the characteristics of the organization, employee needs, and the accompanying social dynamics. Therefore, effective leaders are those who are able to adjust their leadership approach flexibly and strategically. This study emphasizes the importance of developing adaptive, professional, and moral leadership in order to face the challenges of modern organizations, especially in the world of education.